Some studies on the propagation of waves in a viscoelastic medium - Çolpan, Oya. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1986., 1986)
In this study, the general theory of viscoelastic surface waves, the effects of initial stress on the reflection and refraction of plane waves, plane Lamb's problem ina viscoelastic medium under the influence of gravity and the propagation of plane waves in a viscoelastic plate under the influence of gravity are considered. Some special types of waves such as Love and Rayleigh waves are also included. In each case, a viscoelastic medium of Voigt type whfch is often represented by a parallel spring - dashpot model is used. Wave-velocity equations and the amplitude ratios of the reflected and the refracted waves to the incident wave are deduced. The imaginary part of the complex wave-velocity is neglected since it has a very small value when compared with the real part when the retardation time T of the medium is less than 10 seconds.
Keywords: Viscoelasticity.; Wave-motion, Theory of.